Cost of Water Use for Negotiating Rates in Energy Exchanges : Evidence from the Hydroelectric Industry (2020)
ABSTRACT: This paper analyzes the importance of the cost of dam water use in hydroelectric generators according to the International Financial Reporting Standard (IFRS) and Management Accounting. Not valuing the use of water from dams would imply undervaluing energy generation service, leading to a lack of reasonability in the Financial Statements of electricity generators. For this reason, it is vital to recognize that dam water has a cost that directly impacts the Statement of Financial Position as an asset and later, in energy generation and commercialization, its cost will impact the statement of profit or loss, according to the IFRS as good accounting and financial practices around the world. Said cost will also be an important indicator for rationalizing consumption, defining public policy, or determining energy tariffs. An empirical study is conducted for Colombia and Norway, two of the main countries in the world whose primary source of energy generation is water. The results evidence the need for hydroelectric generators to present the cost of their hydric reserve as intangibles inventories because of its potential capacity to generate electric power. Additionally, there is a positive and significant relationship between the cost of water and the price of energy, and a negative relationship between the price of energy and dam levels.